AKUNTABILITAS DAN TRANSPARANSI PADA PENGELOLAAN DANA DESA DI KABUPATEN BEKASI - Ukhtiana Nur Arba’I Choirunnisa; Heni Yusnita (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
This study was conducted to test whether there is an influence between accountability and transparency on village fund management in Kabupaten Bekasi. The population in this study was the financial division of the Village Government in West Java totaling 5,312. The sample size was taken using the Slovin formula which produced a sample size of 30 villages, this study used Partial Least Square (PLS) Analysis using Smart PLS software version 3.0. Based on the results of this study, it shows that villages in Kabupaten Bekasi have implemented accountability and transparency well, so it can be said that accountability has an effect on Village Fund Management because there is a presentation and reporting of financial activities to the authorities, supported by evidence in the accountability report to ensure transparency. Transparency also has an influence on Village Fund Management because the government has provided complete information about what has been done to the community.